Smug1 alleviates the reproductive toxicity of 5-FU through functioning in rRNA quality control - Gerile Naren; Debang Li; Danni Xing; Yu Liu; Lu Wang; Na Fan; Haoran Li; Xue Bai; Xiejun Zeng; Jin Wang; Xihe Li; Siqin Bao; et al. (Scientific Reports)
Abstract 5-Fluorouracil (5-FU) is a widely used chemotherapeutic agent whose incorporation into nucleic acid plays an essential role in its therapeutic efficacy. 5-FU induces severe reproductive toxicity, which has been shown to be reversible. However, the underlying mechanisms have not been fully elucidated. Since single-strand-selective monofunctional uracil-DNA glycosylase 1 (Smug1) is a key enzyme in the excision of 5-FU, we investigated its potential role in the reversible reproductive toxicity of 5-FU by integrating knockdown, overexpression and LC‒MS/MS approaches. 5-FU treatment increased Smug1 and Dkc1 expression but blocked rRNA maturation in preimplantation embryos. Smug1 knockdown inhibited Dkc1 expression and impaired rRNA maturation, leading to reduced preimplantation embryo development. In contrast, Smug1 overexpression alleviated the inhibitory effects of 5-FU on rRNA and oocyte maturation and partially rescued 5-FU-induced developmental defects in preimplantation embryos. LC‒MS/MS analysis further revealed that overexpression of Smug1 reduced the levels of RNA incorporated 5-FUrd, the metabolite of 5-FU, indicating that Smug1 potentially alleviates reproductive toxicity by excising 5-FU from RNA. Our findings revealed the active involvement of Smug1 in counteracting 5-FU-induced reproductive toxicity and provide valuable references for the development of new strategies to reduce the adverse effects of 5-FU.